Withdrawal of sulfonylureas from patients with type 2 diabetes receiving long-term sulfonylurea and insulin combination therapy results in deterioration of glycemic control: a randomized controlled trial - Srivanichakorn, Weerachai (Diabetes Metab Syndr Obes, 2015)
BACKGROUND: The benefit of sulfonylureas (SUs) to patients with type 2 diabetes mellitus receiving long-term insulin treatment is unclear. This study evaluated glycemic control and beta-cell function after SU withdrawal in these patients. METHODS: In this 8-week randomized controlled study, patients with type 2 diabetes who had been treated with insulin for at least 3 years plus moderate to high doses of SUs were randomly assigned to withdrawal (n=16) or continuation (n=16) of SUs. Clinical characteristics, glycemic control, hypoglycemic events, and insulin secretion, including homeostasis model assessment of beta-cell function (HOMA-B) score, C-peptide concentration, and Matsuda index, were evaluated at baseline and after 2 and 8 weeks. RESULTS: Thirty patients (16 in the SU withdrawal group and 14 in the SU continuation group) completed the study. Median duration of diabetes was 17 (range 5–40) years. Baseline clinical characteristics, glycemic control, and HOMA-B were similar in the two groups, but the mean fasting C-peptide concentration was higher in the SU withdrawal group. After 8 weeks, the SU withdrawal group showed a significant increase in mean glycosylated hemoglobin levels from 7.8%±0.5% (62±5 mmol/mol) to 8.6%±1.2% (71±13 mmol/mol; P=0.002), whereas the SU continuation group showed a slight but not significant increase from 7.7%±0.5% (61±5 mmol/mol) to 7.9%±1.2% (63±13 mmol/mol; P=0.37). Insulin secretion, as measured by C-peptide and HOMA-B, decreased by 18% and 36%, respectively, in the SU withdrawal group. Hypoglycemic events were significantly more frequent in the SU continuation group whereas body weight did not change significantly in either group. CONCLUSION: Withdrawal of SU from patients with type 2 diabetes receiving long-term combination treatment with SU and insulin resulted in deterioration of glycemic control and insulin secretion.